Diagnostic Accuracy of Serum Creatine Kinase Muscle Brain Fraction and Lactate Dehydrogenase for Detection of Perinatal Asphyxia in Term Neonates - Aleena Asif, Zunera Riaz Cheema, Farah Naz Tahir, Nazia Zaib, Muhammad Umair Shoukat (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the diagnostic accuracy of serum creatine kinase muscle brain fraction and lactate dehydrogenase for detection of perinatal asphyxia in term neonates using clinical findings as Gold standard Design of the Study: Cross sectional study Study Settings: The study was conducted at Pediatric Department, Lahore General Hospital, Lahore from June 2021 to December 2021. Material and Methods: Demographic information (name, age (in hours), gender, birth weight, and gestational age) was gathered. Under aseptic conditions, blood was taken with a 3cc BD syringe. For CK-MB and LDH testing, samples were sent to the pathology laboratory at the hospital. Two millilitres of clotted blood were tested using reagent kits and auto analyzers. Patients were classified as either positive or negative (according to the operational definition) based on the results of the evaluations of their reports. Results of the Study: In our study, age distribution shows that 63.33%(n=152) were upto 6 hours and 36.67%(n=88) had >6 hours, mean+sd was calculated as 5.60+1.79 hours, 39.17%(n=94) were male and 60.83%(n=146) were females. The diagnostic accuracy of Serum Creatine kinase muscle brain fraction for detection of perinatal asphyxia in term neonates using clinical findings as gold standard was recorded as 93.59% sensitivity, 66.67% specificity, 99.10% positive predictive value, 21.05% negative predictive value and 92.92% accuracy rate. Conclusion: For detecting prenatal asphyxia in term infants, the diagnostic accuracy of serum creatine kinase muscle brain fraction and lactate dehydrogenase (LDH) is useful, however LDH is more accurate than serum creatine kinase muscle brain fraction